The matrix effect on generation of quasi-three-level continuous wave neodymium laser under inhomogeneous pumping - Gerаsimenko, Vаleryiа I.; Stаshkevitch, Ihаr V. (Journal of the Belarusian State University. Physics, 2019)
The main generation characteristics of a neodymium-doped laser with a quasi-three-level scheme are analyzed for most common crystalline matrices. The energy characteristics of radiation from such a laser with different matrices in the stationary mode are studied theoretically. The operation of both the end-pumped and transversely-pumped laser has been simulated. The results of the calculations show that allowance for the spatial inhomogeneity of the pump beam, both for longitudinal and transverse excitation, leads to the increased calculated value of the pump threshold power and to the decreased generation efficiency parameter compared to the results for the point model of laser. It is demonstrated that the two matrices YAG and GGG have optimal threshold pump powers and slope efficiencies due to lower reabsorption losses.
Keywords: neodymium laser; quasi-three-level scheme; spatial beam inhomogeneity; slope efficiency; pump power threshold; Nd : KGW; Nd : GVO; Nd : YVO; Nd : YAG; Nd : GGG; Nd : YAP